Retzius’ space haematoma after spontaneous delivery: a case report - Fieni, S.; Berretta, R.; Merisio, et al., C. (Acta Biomedica Atenei Parmensis, 2005)
We report a case of a haematoma of the Retzius space after spontaneous uncomplicated delivery. In the postpartum period, the patient complained of urinary retention and pain in the hypogastric region radiating to her left hip and leg. The ultrasound examination showed the presence of 160x100x80mm confluent solid and liquid areas with peripheral vascularization. At exploratory laparotomy a haemorrhagic infiltration was found in Retzius’ space and the anterior wall of the bladder, which appeared thickened and swollen below the peritoneum.We tried to drain the haematoma, however, we failed to drain it completely because of the large blood infiltration in the bladder wall. Clinical and ultrasound follow-up examinations showed a progressive reduction of the haematoma which completely disappeared nine months later. The haemodynamic changes occurring during pregnancy and labour, associated with strong mechanical stress, seem to be among the major causative factors of haematoma formation. Moreover, the venous load in the pelvic vascular system is increased during pregnancy; a stress-induced increase in venous blood pressure might play a prominent role, especially in cases of venous ectasia, where the resistance of blood vessel walls is reduced. Intraoperative evidence seemed to suggest a haemorrhage secondary to the rupture of the venous vessels in the Santorini plexus. The rupture was probably caused by the thrust of the fetal head, associated with abnormality or fragility of the blood vessels, or by some pathologic changes occurring in the anatomical structures during pregnancy, which could not be accurately defined because of the severity and degree of the haematoma infiltration found intraoperatively.